2006
DOI: 10.2337/diabetes.55.02.06.db05-0997
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TUB as a Novel Candidate Gene Influencing Body Weight in Humans

Abstract: Previously, we identified a locus on 11p influencing obesity in families with type 2 diabetes. Based on mouse studies, we selected TUB as a functional candidate gene and performed association studies to determine whether this controls obesity. We analyzed the genotypes of 13 single nucleotide polymorphisms (SNPs) around TUB in 492 unrelated type 2 diabetic patients with known BMI values. One SNP (rs1528133) was found to have a significant effect on BMI (1.54 kg/m 2 , P ‫؍‬ 0.006). This association was confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…Thus, the current study of 892 DZ pairs and an additional 418 MZ pairs and 94 DZ singletons provided even greater power. Table 2 shows genotype and allele frequencies of the three SNPs in our cohort, which are compatible with the study by Shiri-Sverdlov et al [5]. Pairwise LD, quantified by r 2 , was modest for all pairwise combinations of the three SNPs: rs2272382 vs rs2272383: 0.17; rs2272382 vs rs1528133: 0.02; rs2272383 vs rs1528133: 0.09.…”
Section: Snp Genotypingsupporting
confidence: 77%
See 4 more Smart Citations
“…Thus, the current study of 892 DZ pairs and an additional 418 MZ pairs and 94 DZ singletons provided even greater power. Table 2 shows genotype and allele frequencies of the three SNPs in our cohort, which are compatible with the study by Shiri-Sverdlov et al [5]. Pairwise LD, quantified by r 2 , was modest for all pairwise combinations of the three SNPs: rs2272382 vs rs2272383: 0.17; rs2272382 vs rs1528133: 0.02; rs2272383 vs rs1528133: 0.09.…”
Section: Snp Genotypingsupporting
confidence: 77%
“…The aim of our study was to replicate the previously observed associations with the three TUB SNPs in diabetic patients and individuals enriched for type 2 diabetes [5] in a large sample of Europid female twins from the general population. We report confirmation of association of rs2272382 with measures of general and central obesity, but only in postmenopausal women, which accords with the association of the mouse homologue Tub with late-onset obesity.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations